2009
DOI: 10.1016/j.jeconom.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of state price densities

Abstract: Ambiguity, also called Knightian or model uncertainty, is a key feature in financial modeling. A recent paper by Maccheroni et al. (2004) characterizes investor preferences under aversion against both risk and ambiguity. Their result shows that these preferences can be numerically represented in terms of convex risk measures. In this paper we study the corresponding problem of optimal investment over a given time horizon, using a duality approach and building upon the results by Schachermayer (1999, 2001). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For example, the idea of Yatchew and Hardle [18] is to use nonparametric least squares method and Bootstrap method to consider tail constraints under the condition of the call option price to find better the effect of getting the tail constraint. Hardle and Hlavka [19] and Birke and Pilz [20] have further studied the nonparametric estimation method under call option pricing no-arbitrage constraints but only for the different estimation method. Monteiro and Santos [21] have established a nonparametric regression model with both call and put option data, which has been transformed into a quadratic programming model to solve it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the idea of Yatchew and Hardle [18] is to use nonparametric least squares method and Bootstrap method to consider tail constraints under the condition of the call option price to find better the effect of getting the tail constraint. Hardle and Hlavka [19] and Birke and Pilz [20] have further studied the nonparametric estimation method under call option pricing no-arbitrage constraints but only for the different estimation method. Monteiro and Santos [21] have established a nonparametric regression model with both call and put option data, which has been transformed into a quadratic programming model to solve it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, over the last decades, Wolfgang Karl Härdle has made many seminal contributions to applicable semiparametrics, both from theoretical and applied perspectives. These contributions range from robust nonparametric regression (Härdle 1984a, b;Marron 1985a, b, 1990a, b;Härdle and Gasser 1985;Härdle and Kelly 1987;Härdle et al , 1992aHärdle and Bowman 1988;Härdle and Tsybakov 1988;Härdle and Vieu 1992;Härdle and Mammen 1993), over single index models Horowitz and Härdle 1996), real steps into computational statistics (Müller et al 1997;Klinke et al 1997;Härdle et al 2001), true applicable semiparametrics (Liang et al 1999;Hall et al 2000;Wang et al 2004) to the development of dynamic semiparametric factor models (Fengler et al 2007;Brüggemann et al 2008;Park et al 2009;Härdle and Hlavka 2009). The conducted work has not only a strong theoretical background, but also solid empirical justification, which makes the methods developed by Wolfgang Karl Härdle highly valuable.…”
Section: Applicable Semiparametricsmentioning
confidence: 99%
“…Instead of an integrated criterion also an averaged criterion like the mean average squared error (MASE) can be used which replaces integration with summation in (16). When using a second order kernel straightforward calculations yield…”
Section: Selection Of Smoothing Parametermentioning
confidence: 99%
“…Li (1987) showed that each of the above three criteria leads to an optimally selected L in the sense that they all minimize the asymptotic weighted integrated squared error (see (16)). In this sense the obtained L are asymptotically equivalent.…”
Section: Choice Of Tuning Parametersmentioning
confidence: 99%